Analysis of consumer preferences for prepaid mobile internet packages in Iran: A Discrete Choice Experiment - Arya Sohrabi; Mir Saman Pishvaee; Ashkan Hafezalkotob; Shahrooz Bamdad (Universitas Islam Indonesia, 2020)
As a first discrete choice experiment in Iran emerging telecommunication market, this paper studies consumer preferences for prepaid mobile internet packages with a combined software and paper-based interview. A two-stage Bayesian D-optimal design procedure is deployed to design choice sets of mobile internet packages from four main attributes. The utility structure and customers’ willingness-to-pay for mobile internet packages are analyzed. Findings/originality: The results indicate that even with a considerable price reduction, consumers avoid prepaying for data plans with commitment periods longer than six months and high traffic volume. Traffic volume and brand attributes are recognized as the two most influential factors on consumers’ behavior. Simulating the market demonstrates the competition between mobile internet operators in Iran market. The statistics express a significant effect of consumers’ current mobile operator on their preferences for the brand attribute.